Analysis of Olig2 and YKL-40 expression: a clinicopathological/immunohistochemical study for the distinction between subventricular zone II and III glioblastomas - Batista, Kelvin Manuel Piña; Costa, Bruno Augusto Lourenco; Herreros, Isabel Cuervo-Arango; Vega, Ivan Fernandez; Morales, Julio Cesar Gutierrez; Alvarez, Aitana Vallina; Marron, Pablo Isidro; Meilán, Ángela; Astudillo, Aurora; Alvarez, Kenia Yoelvi (Folia Neuropathologica, 2016)
Glioblastomas (GBs) are the most common and lethal primary brain tumors in the adults. Glioblastomas originates either from astrocytes that have accumulated mutations and de-differentiated or from neural stem cells within the subventricular zone (SVZ) in close contact with the vasculature. Recently, several studies have hypothesized that gliomagenesis occurs in perivascular niches with highly invasive peripheral proliferating zones. The purpose of our study was to investigate the pathological and clinical significance of Olig2 and YKL40 immunoexpression in 152 GBs in relationship to the SVZ II and III. Olig2 expressions were successfully detected in 12 (15.58%) of 77 SVZ type II GBs and 16 (21.3%) of 75 SVZ type III GBs, respectively. YKL-40 expression was observed in 45 (58.4%) of 77 SVZ type II GBs and in 17 (22.6%) of 75 SVZ type III GBs, respectively. Stepwise multivariate Cox proportional hazards models were used, and the prognostic factors to significantly impact OS were: PFS < 54 weeks (HR: 5.86; CI: 3.02-11.33; p = 0.00); radiotherapy (HR: 0.34; CI: 0.18-0.60; p = 0.00); radio- and chemotherapy (HR: 0.05; CI: 0.03-0.10; p = 0.0), and YKL-40+ GBs (HR: 1.61; CI: 1.28-2.31; p = 0.01).